THE EFFECT OF LONG CARBONIZATION TIME ON QUALITY OF CHINESE WATER CHESTNUT ACTIVATED CHARCOAL AS A PEAT WATER BIOFILTER - Noor Khamidah; Muhammad Imam Nugraha; Norinayati Norinayati (Universitas Lambung Mangkurat, 2022)
The purpose of this study was to determine whether chinese water chestnut (Eleocharis dulcis) could be used as activated charcoal as a peat water biofilter and to determine the effect of carbonization time on the quality of activated charcoal from chinese water chestnut (Eleocharis dulcis). The experimental method used in this study was a single factor Completely Randomized Design (CRD) with 6 treatments, namely differences in carbonization time (30 minutes, 1 hour, 1.5 hours, 2 hours), factory charcoal (positive control) and no treatment. (negative control). The results showed that activated charcoal of chinese water chestnut (Eleocharis dulcis) can be used as a biofilter of peat water and carbonization of 2 hours (A5) is thought to be the most optimal time for the quality of activated charcoal of chinese water chestnut (Eleocharis dulcis) which is indicated by the parameters of ash content of 0.367% and iodine absorption. 1910.126 mg/g.